Analisis Pengembangan Kurikulum Kepesantrenan Dengan Penguatan Wawasan Rasionalisme Kebangsaan, Moderasi Beragama Dan Berparadigma Multikultural - Suprapno, Suprapno; Hifdzil Haq, Ahmad; Amin, Alfauzan; Noer Aly, Hery; Rohimin, Rohimin (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
Pesantren as the oldest institution in Indonesia has a big responsibility in caring for diversity through national insight and mediation education with a multicultural paradigm. This responsibility can be realized through the education system which is mainly related to the educational curriculum provided by the pesantren. This study seeks to analyze the development of the pesantren curriculum through strengthening national insight, religious moderation, and the multicultural paradigm. This study uses a qualitative approach with the type of library research. The results of this study indicate that the pesantren curriculum basically includes the hidden curriculum and the core curriculum. The curriculum applied by the pesantren is integrated with the values ​​of love for the homeland, diversity, religious moderation, and a multicultural paradigm. The existence of santri who come from different regions, ethnicities, and ethnicities allows pesantren to carry out a multicultural education system. Fostering human beings with character, morals, having human values, compassion, courtesy, and peace as well as respect for differences are an inseparable part of the applied education pattern. by upholding the value of diversity and difference. Therefore, through the developed curriculum, Islamic boarding schools are able to become educational institutions that are ready to face various challenges in order to avoid the potential for major conflicts with racial issues.